The Application of Time-Driven Activity Based Costing System on Inductors in Electrics and Electronics Industry - Filzah Lina, Mohd Safeiee; Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Nurul Farahin, Zamrud (Springer, 2020)
The adoption of traditional costing system (TCS) in manufacturing industry has motivated the need for improvements in the accounting system. The main problem of TCS is the inability to provide useful feedback to understand and allocate overhead costs and inaccurate to forecast on unused capacity. To perform this study, Time-driven activity-based costing (TDABC) is well suited for manufacturing industry, involving many activities with complex time drivers. TDABC is a variation and expansion of activity based costing where by process costs are analyzed based on time and resource consumption. TDABC seems to be one of the best tools for understanding cost behavior and for refining a cost system. This study is to apply TDABC method on electrics and electronics industry system. This improvement is to maximize the efficiency and effectiveness throughout the production system, cost and eventually increase the net income. From this work the information about cost and profitability quickly get and inexpensively. Several generally accepted methods of cost accounting have been described, of which TDABC is considered the most sophisticated and precise.